THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES OF ADOLESCENTS IN EFFORTS TO PREVENT ADOLESCENT PREGNANCY - Susanti, Rosa; Siti Fatimah, Okta Zenita (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
A critical issue during adolescence is reproductive health, particularly teenage pregnancy. One of the factors contributing to teenage pregnancy is the low level of knowledge among adolescents about sexuality and reproductive health, which can lead to negative behaviors. Adolescents' knowledge and attitudes are crucial in efforts to prevent teenage pregnancy. This study aims to determine the relationship between adolescents’ knowledge and attitudes in preventing teenage pregnancy. This research consists of three stages: preparation, implementation, and evaluation. The study was conducted at MA Al-Ihsan, Pondok Gede, over an effective period of three weeks in August 2024. The research method used was quantitative with a cross-sectional approach. The data used in this study were primary data, collected from 99 students (both male and female) at MA Al-Ihsan, using total sampling. The data analysis technique applied was the Chi-Square test. The results of the study indicate that knowledge plays a significant role in shaping adolescents' attitudes toward preventing pregnancy. These findings highlight the importance of early reproductive health education. In conclusion, there is a significant relationship between knowledge and adolescents’ attitudes in the effort to prevent teenage pregnancy.